Management of a cluster of Clostridium difficile infections among patients with osteoarticular infections. Issue 1 (December 2017) - Färber, Jacqueline; Illiger, Sebastian; Berger, Fabian; Gärtner, Barbara; Müller, Lutz; Lohmann, Christoph; Bauer, Katja; Grabau, Christina; Zibolka, Stefanie; Schlüter, Dirk; Geginat, Gernot
Abstract Background Here we describe a cluster of hospital-acquiredClostridium difficile infections (CDI) among 26 patients with osteoarticular infections. The aim of the study was to define the source ofC. difficile and to evaluate the impact of general infection control measures and antibiotic stewardship on the incidence of CDI. Methods Epidemiological analysis included typing ofC. difficile strains and analysis of possible patient to patient transmission. Infection control measures comprised strict isolation of CDI patients, additional hand washings, and intensified environmental cleaning with sporicidal disinfection. In addition an antibiotic stewardship program was implemented in order to prevent the use of CDI high risk antimicrobials such as fluoroquinolones, clindamycin, and cephalosporins. Results The majority of CDI (n  = 15) were caused byC. difficile ribotype 027 (RT027). Most RT027 isolates (n  = 9) showed high minimal inhibitory concentrations (MIC) for levofloxacin, clindamycin, and remarkably to rifampicin, which were all used for the treatment of osteoarticular infections. Epidemiological analysis, however, revealed no closer genetic relationship among the majority of RT027 isolates. The incidence of CDI was reduced only when a significant reduction in the use of fluoroquinolones (p  = 0.006), third generation cephalosporins (p  = 0.015), and clindamycin (p  = 0.001) was achieved after implementation of an intensified antibiotic stewardship program which included a systematic review of all antibiotic prescriptions. Conclusion The successful reduction of the CDI incidence demonstrates the importance of antibiotic stewardship programs focused on patients treated for osteoarticular infections.